Pattern-induced visual discomfort and its cumulative effects revealed by pupillary measures - Meidan, Ron; Bonneh, Yoram S. (Frontiers in Human Neuroscience, 2026)
IntroductionViewing repetitive striped patterns can induce pattern glare, experienced as visual discomfort (VD). While previous studies examined either pupillary responses or VD separately, few have investigated how they covary or evolve with repeated exposure. This study tested whether pupillary dynamics could serve as potential physiological indicator of individual visual sensitivity beyond subjective reports.MethodsAcross four experiments (preliminary: n = 97; main: n = 70 for spatial frequency, n = 46 for central field size, n = 36 for central blank, with partial overlap), we manipulated spatial frequency, central field size, and surround field size of square-wave gratings (0.5–3 s) while measuring both discomfort and pupil size.ResultsHigher spatial frequencies and larger pattern areas elicited stronger pupillary constriction and greater discomfort, whereas repeated exposures produced cumulative increases in discomfort and decreases in baseline pupil size, consistent with visual strain rather than adaptation. To assess the potential of pupillometry as an indicator of visual discomfort, we examined individual differences in the main spatial-frequency experiment (controlled viewing distance, n = 42). A paradoxical pattern emerged: within participants, stronger stimuli produced greater constriction, but individuals with higher overall discomfort showed weaker constriction and stronger late redilation. Similar dissociations between subjective sensitivity and pupillary responses have been noted in studies of light-induced discomfort, suggesting that related mechanisms may contribute, although their specific physiological basis remains unclear.DiscussionOverall, our findings clarify how pattern-induced discomfort evolves over time and across individuals and highlight pupillometry's potential as a sensitive, physiological tool for assessing visual sensitivity.